Peningkatan Kemampuan Petani Menangani Kegawatdaruratan Tersedak Akibat Obstruksi Benda Asing Melalui Pelatihan Hidup Dasar: Peningkatan Kemampuan Petani Menangani Kegawatdaruratan Tersedak Akibat Obstruksi Benda Asing Melalui Pelatihan Hidup Dasar - Syaifuddin Kurniato; Arista Maisyaroh; Eko Prasetya Widianto; Kartika Nurhayati (Jurnal Keperawatan Terapan, 2026)
Farmers represent a professional group frequently exposed to workplace emergencies. During agricultural activities, inhalation of dust and fine particles can lead to sudden airway obstruction, severely compromising respiratory function. To prevent fatal outcomes, farmers require structured knowledge and practical skills in immediate response, including basic cardiopulmonary resuscitation and choking management. This study aimed to analyze the effect of basic life support training on improving farmers’ competence in handling choking incidents caused by foreign body obstruction. A pre-experimental design with a one-group pre-test and post-test approach was employed. The sample comprised 30 participants, calculated using the Slovin formula and selected through purposive sampling. Pre- and post-intervention assessments revealed significant improvements in participants’ ability to manage choking emergencies. The Wilcoxon signed-rank test confirmed a statistically significant difference (p < 0.001). These findings demonstrate that structured training effectively enhances first-aid capabilities for respiratory emergencies. Integrating simulation-based practice into community programs is recommended to strengthen response readiness and improve overall safety awareness among agricultural workers. Keywords: Airway obstruction, Cardiopulmmonary resuscitation, Emergencies, Farmers